Flow Injection- Spectrophotometric Determination of Salbutamol Sulphate and Pyridoxine Hydrochloride Using 2,4-Dinitrophenylhydrazine - Al-Abachi, Mouyed; Subhi, Sadeem (Iraqi Journal of Science, 2023)
A batch and flow injection (FI) methods with spectrophotometric detection is proposed for determining of two of phenolic drugs: salbutamol sulphate(SLB)and pyridoxine hydrochloride(PYD) in pure and in pharmaceutical formulations. The methods utilized an oxidative-coupling reaction based upon oxidation of 2,4-dinitrophenylhydrazine (DNPH) with sodium periodate, where an electrophilic intermediate (diazonium salt of the reagent) is produced, which couples with either SLB or PYD in the presence of sodium hydroxide yielding a highly colored condensation product. The absorbance is measured after 15min at 525and515 nm for SLB and PYD respectively. Calibration graphs for both batch and FIA methods were linear over the concentration ranges of 1-24μg/ml for SLB and 0.4-16μg/ml for PYD, and of 30-1100μg/ml for SLB and20-1200μg/ml for PYD respectively. A detection limits of 0.580μg/ml SLB and 0.150μg/ml PYD for batch method, and 15.32μg/ml SLB and12.21μg/ml PYD for FIA method. The proposed methods were applied successfully to the determination of SLB and PYD in pharmaceutical preparations and were compared statistically with reference methods by means of t- test and F- test and were found not to differ significantly at 95% confidence level. The procedures are characterized by its simplicity, accuracy and precision. The results obtained were in good agreement with those obtained using reference methods for comparison.